Гамма випромінювання залишків наднових зір - Петрук, О. (Праці наукового товариства ім. Шевченка, 2011)
History of gamma ray astronomy is shortly reviewed. Information on the observations of supernova remnants in gamma- rays as well as on the studies of Ukrainian scientists in this field is presented. Gamma ray emission is detected from 14 out of 274 supernova remnants in our Galaxy. These objects are visible for modern means of observations in photons with energies >0.1 GeV only; maps of their surface brightness distribution are published. A method of synthesizing the redicted gamma ray image of a supernova remnant from its radio and X- ray maps is described and applied to a supernova remnant SN 1006.